Duma, yuan, and beyond: conceptualizing parliaments and parliamentarism in and after the Russian and Qing Empires - Sablin, Ivan; Moniz-Bandeira, Egas; Badagarov, Jargal; Dorn, Martin; Sodnomova, Irina (Planting parliaments in Eurasia, 1850-1950, 2021)
The chapter focuses on two new institutions, the State Duma (Gosudarstvennaia duma) and Political Consultative Council (Zizhengyuan), which were introduced in the Russian and Qing Empires, when the two imperial formations joined the global constitutional transformations. The names of the two bodies pointed to the statist (etatist) rather than popular connotations of the new institutions. Furthermore, the State Duma and the Zizhengyuan were often explicitly distinguished from a Western parliament, even though the latter as a generalized notion was undoubtedly the main point of reference during the attempted imperial modernizations. Seeking to expand the current debate on the conceptual history of parliamentarism by including non-European histories, this chapter charts the genealogies of the two terms and positions them in the discussions of parliamentarism during the modernizations of the Russian and Qing Empires and during the post-imperial settlements.
Gesehen am 28.06.2021